2012
DOI: 10.1080/00268976.2012.655334
|View full text |Cite
|
Sign up to set email alerts
|

Study of group velocity in the negative refractive index region in three level closedΛsystem via spontaneously generated coherence

Abstract: A new approach is suggested to realize simultaneous negative permittivity and permeability in a three level closed system with incoherent pumping via spontaneously generated coherence (SGC). In this system the negativity of the real part of magnetic permeability can be achieved in the presence of SGC whereas in the absence of SGC it is positive. Thus the SGC makes the system a negative index medium (NIM) in a band of frequency range. The position and the band of the frequency region of negative refraction can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It has been reported on the group index of a material with a negative refractive index and no absorption. Through the use of SGC and the incoherent pumping effect, the group index of a medium with a negative refractive index has also been examined in three-level atomic systems [35].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported on the group index of a material with a negative refractive index and no absorption. Through the use of SGC and the incoherent pumping effect, the group index of a medium with a negative refractive index has also been examined in three-level atomic systems [35].…”
Section: Introductionmentioning
confidence: 99%
“…One of the exciting phenomena generated by quantum coherence and interference in various systems as electromagnetically induced transparency (EIT) has been widely studied during the past two decades [1][2][3][4][5][6][7][8]. In addition to eliminated probe resonant absorption, EIT can create superluminal to subluminal (or vice versa) light propagation, for weak probe light propagates inside a medium [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum coherence and interference phenomena have been studied by many research groups in past decades due to their potential applications in quantum information science and the development of all-optical devices [1][2][3][4][5]. The control of the absorption, dispersion and group velocity of transmitted light from dispersive media has attracted a lot of attention in recent years in view of its potential application in quant um information processing [6][7][8]. It is shown that coherent control of the optical properties of a dispersive medium leads to new phenomena such as electromagnetically induced transparency (EIT) [9][10][11], lasing without inversion [12] and enhancement of refraction index [13].…”
Section: Introductionmentioning
confidence: 99%